2021
DOI: 10.1002/hep.31561
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of Cannabinoid Receptor Interacting Protein 1 Promotes Pathogenesis of Intrahepatic Cholangiocarcinoma Through Suppressing Parkin‐Dependent Pyruvate Kinase M2 Ubiquitination

Abstract: BaCKgRoUND aND aIMS: Methylation landscape is important for maintaining the silence of cannabinoid receptorinteracting protein 1 (CNRIP1) in some tumors. However, the role of CNRIP1 in intrahepatic cholangiocarcinoma (ICC) remains poorly defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
0
12
1
Order By: Relevance
“…USP20 can deubiquitinate PKM2 without affecting PKM2 expression [36]. Chen et al reported that Parkin modulated protein degradation of PKM2, while Liu et al found that Parkin ubiquitylated PKM2 at K186 and K206 to inhibit enzymatic activity of PKM2 without affecting PKM2 stability [34,37]. Viana et al [39] observed that laforin/malin E3 ligase complex catalyzes K63-linked ubiquitination of PKM2, which interferes with the localization of PKM2 to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…USP20 can deubiquitinate PKM2 without affecting PKM2 expression [36]. Chen et al reported that Parkin modulated protein degradation of PKM2, while Liu et al found that Parkin ubiquitylated PKM2 at K186 and K206 to inhibit enzymatic activity of PKM2 without affecting PKM2 stability [34,37]. Viana et al [39] observed that laforin/malin E3 ligase complex catalyzes K63-linked ubiquitination of PKM2, which interferes with the localization of PKM2 to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination is another common and essential type of post‐translational modification; however, its functions in the regulation of PKM2 oligomers are still poorly known. PKM2 was reported to interact with E3 ligases including Parkin, CHIP, TRIM58, and laforin/malin complex, as well as DUBs including HAUSP and USP20 [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. CHIP and HAUSP participate in the regulation of ubiquitination and stability of PKM2 protein [ 35 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parkin mediates the ubiquitination of PKM2 and reduces its enzymatic activity ( Liu et al, 2016 ). Overexpression of cannabinoid receptor-interacting protein 1 (CNRIP1) activates Parkin, leading to PKM2 degradation and thereby promoting cell growth and metastasis in intrahepatic cholangiocarcinoma (ICC) ( Chen D. et al, 2021 ). OTUB2, an OTU deubiquitinating enzyme, directly interacts with PKM2.…”
Section: Ubiquitination Sumoylation and Glucose Metabolism In Cancermentioning
confidence: 99%
“…Previous studies have demonstrated that epigenetic modifications are involved in the development and progression of CRC, altering the gene expression without changing the original DNA sequence ( 6 ). DNA methylation, which is a common epigenetic modification, occurs mainly in promoter regions and often drives gene silencing ( 7 , 8 ). The methylation modifications of specific genes are correlated with the progression of CRC ( 9 ).…”
Section: Introductionmentioning
confidence: 99%